2008
DOI: 10.1371/journal.pone.0002601
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Feeding Controls Fetal Biological Clock

Abstract: BackgroundIt is widely accepted that circadian physiological rhythms of the fetus are affected by oscillators in the maternal brain that are coupled to the environmental light-dark (LD) cycle.Methodology/Principal FindingsTo study the link between fetal and maternal biological clocks, we investigated the effects of cycles of maternal food availability on the rhythms of Per1 gene expression in the fetal suprachiasmatic nucleus (SCN) and liver using a transgenic rat model whose tissues express luciferase in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 33 publications
2
44
1
Order By: Relevance
“…1. Previous studies have suggested that the fetus in the uterus uses maternal signals to adapt the fetal biological clock to the maternal environment (Reppert and Schwartz 1983;Davis and Gorski 1988;Parraguez et al 1996;Kennaway 2002;Ohta et al 2002Ohta et al , 2003Ohta et al , 2008Sládek et al 2004;Li and Davis 2005;Saxena et al 2007). These signals are considered to be a variety of nonphotic stimuli including circadian fluctuations in hormonal and nutritional signals from the mother, placental filtering of those signals, and uterine motility (Serón-Ferré et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1. Previous studies have suggested that the fetus in the uterus uses maternal signals to adapt the fetal biological clock to the maternal environment (Reppert and Schwartz 1983;Davis and Gorski 1988;Parraguez et al 1996;Kennaway 2002;Ohta et al 2002Ohta et al , 2003Ohta et al , 2008Sládek et al 2004;Li and Davis 2005;Saxena et al 2007). These signals are considered to be a variety of nonphotic stimuli including circadian fluctuations in hormonal and nutritional signals from the mother, placental filtering of those signals, and uterine motility (Serón-Ferré et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Photon counts from each culture were detrended with a 2-h running average as described previously (Yamazaki et al 2000) with modifications using exmax software (gift from Mr. Tuyoshi Yaita and Dr. Shigenobu Shibata, Waseda University, Tokyo, Japan) (Hayasaka et al 2007;Ohta et al 2008;Hirao et al 2009). The period of Per1-luc activity (recorded from 12 to 84 h in vitro) was assessed for each SCN culture and calculated by averaging the period between the first and second peaks and the period between the second and third peaks as previously described (Yamazaki et al 2000;Ohta et al 2005).…”
Section: Assessment Of Per1-luc Circadian Periods and Phases Of The Umentioning
confidence: 99%
See 3 more Smart Citations